tert-Butylhydroperoxide-Mediated Oxidation of Carbazole-3-carboxyaldehydes - Meesala, Ramu; Arshad, Ahmad Saifuddin Mohamad; Pichika, Mallikarjuna Rao; Mordi, Mohd Nizam; Mansor, Sharif Mahsufi (Synlett, 2018)
Oxidation of carbazole-3-carboxyaldehydes promoted by a 70% aqueous solution of tert-butylhydroperoxide leads to the corresponding carbazole-3-carboxylic acids in good yields. This transition-metal-free oxidation protocol is attractive for the synthesis of pharmaceutically important carbazole analogues.
Keywords: oxidation; carbazole-3-carboxyaldehyde; carbazole-3-carboxylic acid; tert-butylhydroperoxide; dimethyl sulfoxide (DMSO)